Nonthermal pasteurization of pitaya (Hylocereus polyrhizus) juice using the hurdle concept - Halim, H.; Mohd Adzahan, Noranizan; Sobhi, Babak; Sew, Chang Chew; Karim, Roselina; Osman, Azizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Red pitaya juice (RPJ) was subjected to UV-C irradiation and the potential of UV as a pasteurization tool for reducing microbial load in pitaya juice was evaluated. Effectiveness of the hurdle concept, i.e. addition of citric acid (CA) and dimethyl dicarbonate (DMDC) was also studied. Total plate counts (TPC) and yeast and mould counts (YMC) achieved 2.43 log10 and 2.7 log10 reductions respectively after exposure to UV irradiation. Addition of the CA (0.5-2.0%) and dimethyl dicarbonate (DMDC) (5-20 μL/100mL) to pitaya juice reduced the microbial loads, with 1.5% CA and 15 μL/100mL DMDC being the most effective concentrations. Addition of CA and DMDC into RPJ prior to UV treatment achieved significantly higher microbial reduction compared to UV alone, which were 4.12 log10 and 4.14 log10 reductions for TPC and for YMC, respectively.